Short-Term and Procedural Memory for Colours and Inferior Temporal Cortex Activity - E. Castro-Sierra; E. Paredes-Díaz; J. A. Lazareff (Behavioural Neurology)
Two children (male, 10 years, and female, 13 years one month) with tumours of the inferior temporal (IT) cortex of the brain were studied post-surgically for their abilities to carry out a short-term memory test. This involved: differences in colour, number and shape of small plastic objects; differences in receptacles where these objects should be placed and in ways in which this placement should be done; a procedural task involving differences either in colour or in size of wooden rings employed in the task. Their performances in these tests, and those of patients with tumours of other encephalic areas, were compared with the performances of normal controls. The subjects with IT tumours spent a significantly greater amount of time than normal subjects of their age in carrying out the procedural task involving differences in colour. One of the IT subjects also spent a significantly greater amount of time in the procedural task involving size differences. Other differences in the performances of patients with encephalic tumours and the performances of normal controls were not significant. Results are discussed in relation to findings of colour and size perception and memory localized to the inferior temporal and middle temporal cortices.